Westonci.ca is the premier destination for reliable answers to your questions, brought to you by a community of experts. Explore our Q&A platform to find reliable answers from a wide range of experts in different fields. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.
Sagot :
Sure, let's solve the given system of linear equations step by step using the method of elimination or substitution.
We are given the system:
[tex]\[ \begin{cases} 3x + 2y = -1 \\ 2x - 5y = 31 \end{cases} \][/tex]
### Step 1: Eliminate one of the variables
We can eliminate [tex]\( y \)[/tex] by finding common coefficients for [tex]\( y \)[/tex] in both equations, and then subtracting or adding the equations.
Let's multiply the first equation by 5 and the second equation by 2 so that the coefficients of [tex]\( y \)[/tex] in both equations are opposites:
[tex]\[ \begin{cases} 5(3x + 2y) = 5(-1) \\ 2(2x - 5y) = 2(31) \end{cases} \][/tex]
This simplifies to:
[tex]\[ \begin{cases} 15x + 10y = -5 \\ 4x - 10y = 62 \end{cases} \][/tex]
### Step 2: Add the equations to eliminate [tex]\( y \)[/tex]
Now we add the two new equations together:
[tex]\[ (15x + 10y) + (4x - 10y) = -5 + 62 \][/tex]
Simplifying this:
[tex]\[ 15x + 4x + 10y - 10y = 57 \][/tex]
This reduces to:
[tex]\[ 19x = 57 \][/tex]
### Step 3: Solve for [tex]\( x \)[/tex]
Divide both sides by 19 to solve for [tex]\( x \)[/tex]:
[tex]\[ x = \frac{57}{19} \][/tex]
[tex]\[ x = 3 \][/tex]
### Step 4: Substitute [tex]\( x \)[/tex] back into one of the original equations
Now that we have [tex]\( x = 3 \)[/tex], substitute it back into the first original equation to solve for [tex]\( y \)[/tex]:
[tex]\[ 3(3) + 2y = -1 \][/tex]
[tex]\[ 9 + 2y = -1 \][/tex]
Subtract 9 from both sides:
[tex]\[ 2y = -1 - 9 \][/tex]
[tex]\[ 2y = -10 \][/tex]
Divide both sides by 2:
[tex]\[ y = \frac{-10}{2} \][/tex]
[tex]\[ y = -5 \][/tex]
### Solution
Thus, the solution to the system of equations is:
[tex]\[ x = 3,\, y = -5 \][/tex]
So, the solution in coordinate form is:
[tex]\[ (3, -5) \][/tex]
We are given the system:
[tex]\[ \begin{cases} 3x + 2y = -1 \\ 2x - 5y = 31 \end{cases} \][/tex]
### Step 1: Eliminate one of the variables
We can eliminate [tex]\( y \)[/tex] by finding common coefficients for [tex]\( y \)[/tex] in both equations, and then subtracting or adding the equations.
Let's multiply the first equation by 5 and the second equation by 2 so that the coefficients of [tex]\( y \)[/tex] in both equations are opposites:
[tex]\[ \begin{cases} 5(3x + 2y) = 5(-1) \\ 2(2x - 5y) = 2(31) \end{cases} \][/tex]
This simplifies to:
[tex]\[ \begin{cases} 15x + 10y = -5 \\ 4x - 10y = 62 \end{cases} \][/tex]
### Step 2: Add the equations to eliminate [tex]\( y \)[/tex]
Now we add the two new equations together:
[tex]\[ (15x + 10y) + (4x - 10y) = -5 + 62 \][/tex]
Simplifying this:
[tex]\[ 15x + 4x + 10y - 10y = 57 \][/tex]
This reduces to:
[tex]\[ 19x = 57 \][/tex]
### Step 3: Solve for [tex]\( x \)[/tex]
Divide both sides by 19 to solve for [tex]\( x \)[/tex]:
[tex]\[ x = \frac{57}{19} \][/tex]
[tex]\[ x = 3 \][/tex]
### Step 4: Substitute [tex]\( x \)[/tex] back into one of the original equations
Now that we have [tex]\( x = 3 \)[/tex], substitute it back into the first original equation to solve for [tex]\( y \)[/tex]:
[tex]\[ 3(3) + 2y = -1 \][/tex]
[tex]\[ 9 + 2y = -1 \][/tex]
Subtract 9 from both sides:
[tex]\[ 2y = -1 - 9 \][/tex]
[tex]\[ 2y = -10 \][/tex]
Divide both sides by 2:
[tex]\[ y = \frac{-10}{2} \][/tex]
[tex]\[ y = -5 \][/tex]
### Solution
Thus, the solution to the system of equations is:
[tex]\[ x = 3,\, y = -5 \][/tex]
So, the solution in coordinate form is:
[tex]\[ (3, -5) \][/tex]
We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Thank you for trusting Westonci.ca. Don't forget to revisit us for more accurate and insightful answers.